Is finance-growth nexus linear in selected countries of Middle East and Northern Africa? - Chebab, Daouia; Mazlan, Nur Syazwani; Wan Ngah, Wan Azman Saini; Lee, Chin (Center for International Economics, 2020)
The present study re-examines the impact of financial development on economic growth in resource-rich Middle East and North Africa (MENA) countries over 1987-2015. Although several studies investigate the finance-growth nexus, none emphasized the nature of this relationship in MENA. In the long run, an inverted U-shaped association between finance and growth is indicated when using pooled mean group estimations. However, the relationship is not significant in the short run. The outcomes suggest that financial development is significantly and positively affiliated with economic growth up to a certain level. After this turning point, additional financial development tends to adversely affect economic growth. The existence of an inverse U-shape association between financial development and economic growth was confirmed by the estimation of the U-test. The outcomes of our study are important to policymakers, in terms of optimizing the necessary and limit of financial development to ensure maximum benefit for the whole economy through the banking sector.